Individual aerodynamic and physiological data are critical to optimise cycling time trial performance: one size does not fit all - Faulkner, S. H., Jobling, P., Griggs, K. E.; Siegkas, P. (Sports Engineering, 2024)
Cycling time trials are characterised by riders adopting positions to lessen the impact of aerodynamic drag. Aerodynamic positions likely impact the power a rider is able to produce due to changes in oxygen consumption, blood flow, muscle activation and economy. Therefore, the gain from optimising aerodynamics must outweigh the potential physiological cost. The aim was to establish the relationship between energy expenditure and aerodynamic drag, with a secondary aim to determine the reliability of a commercially available handlebar mounted aero device for measuring aerodynamic drag. Nine trained male cyclists volunteered for the study. They completed 4 × 3200 m on an outdoor velodrome where stack height was adjusted in 1 cm integers. The drag coefficient (CdA), oxygen consumption and aerodynamic-physiological economy (APE) were determined at each stack height, with data used to model 40 km TT performance. Small to moderate effect sizes (ES) in response to stack height change were found for CdA, APE and energy cost. The change in TT time was correlated to aerodynamic drag and APE. Meaningful impacts of change in stack height on CdA, APE, energy cost and predicted TT performance, are apparent with highly individualised responses to positional changes.